Stres dan Kelulusan Blok Mahasiswa Perantau dan Nonperantau Tingkat Pertama Kedokteran Universitas Andalas - Putri, Aulia; Ashal, Taufik; Windasari, Noverika; Yulistini; Gusya Liza, Rini; Abdiana (Jurnal Kesehatan Masyarakat Indonesia (JKMI), 2025)
The first year of college presents various challenges, particularly for out-of-town students adapting to independent living without direct family support. Medical students, especially first-years, often face high stress levels. This study examines the relationship between stress levels and module completion rates among out-of-town and local students. An observational analytic method with a cross-sectional design was used, involving 251 first-year Medical Study Program students at Universitas Andalas for the 2023 Academic Year. A total of 162 students met the inclusion criteria, with data collected from June to October 2024. Stress levels were measured using the Medical Student Stressor Questionnaire (MSSQ), and module completion rates for Modules 1.1–1.6 were obtained from academic records. Data were analyzed using the chi-square test. The results showed that 73.5% of respondents were out-of-town students, with severe stress reported by 45.4% of out-of-town and 44.2% of local students. Academic Related Stressors (ARS) were the dominant stress factor. Module completion rates were 68.1% for out-of-town and 69.8% for local students. Bivariate analysis indicated a significant relationship between stress levels and module completion rates (p = 0.002). The study concludes that stress levels significantly affect module completion rates. Students are encouraged to improve time management skills to reduce stress and enhance academic outcomes.